PENGARUH PEMBELAJARAN PAI TERHADAP KEAKTIFAN PESERTA DIDIK MELAKSANAKAN SHALAT FARDHU DI SMAI ALMAARIF SINGOSARI - Dewi Khotmawati; Anwar Sa’dullah; Ahmad Subekti (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to 1) describe the implementation of PAI learning in perfoming fardhu prayers, and to find out wheather there is any influence between the learning of Islamic education on the activity of students in perfoming fardhu prayer at Al-Ma’arif Singosari Islamic High School.2) Data was collected from interviews, questionnaires, documentation, and observation. While data analysis thecniques to test hypotheses using simple linier regression. 3) The results of this study indicate a significant value of at 0,01 < 0,05. So it can be seen that the variable Islamic education learning variable (X) affects the activity of students in Perfoming the Fardhu Variable Prayer (Y).